Le détroit de Gibraltar - Guillaume Le Boedec (EchoGéo)
As they received much media coverage, the assaults on the fences at Ceuta and Melilla in autumn 2005 and the continuous flow of migrants to the Canary Islands in 2006 defined a new perception of migratory phenomena. Since the beginning of the 90’s, the Strait of Gibraltar, the natural limit of Europe, had become the nodal point, the very centre, of transmediterranean illegal immigration. Since the apparition of the common frontier of Schengen, it has caught and spread all legal and technical evolutions set by the European Union to fight illegal migrations. A real testing laboratory for the outsourcing of European migratory policy and of Maghreb cooperation, the Strait of Gibraltar has emerged as a model «frontier-setting» in the Schengen zone, but also as the symbol of its lack of efficiency. Migrants’ resourcefulness and capacity to get round European systems and devices underline the total inefficiency of a closing-the-borders policy led without any plan of developing the countries they come from.